The Use of Animated Video Media on Student Learning Outcomes in the IPAS Subject for Fourth Grade Students at SD Negeri 9 Mamboro - Nuraini Margareta; Abdul Rahman; Nuraini Nuraini; Zulnuraini Zulnuraini; Mas'adi Mas'adi (Journal of Educational Sciences, 2026)
This study aims to determine the effect of using animated video media on student learning outcomes in the IPAS subject for fourth grade students at SD Negeri 9 Mamboro. This study employed a quantitative method using a quasi experimental design, specifically a Nonequivalent Control Group Design (pretest-posttest). The subjects of this study were 38 fourth grade students at SD Negeri 9 Mamboro, comprising an experimental class (IV A) with 20 students and a control class (IV B) with 18 students. The sampling technique used was saturation sampling. The data collection instruments used were achievement tests in the form of pretests and posttests, as well as teacher and student observation sheets as supporting data. Data analysis was performed using an independent samples t test. The results showed that the average posttest score for the experimental class was 73, which was higher than that of the control class, which was 61.88. Furthermore, the results of the hypothesis testing showed a significance value of 0.039 < 0.05, so H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the use of animated video media has a significant effect on student learning outcomes in the IPAS subject for fourth grade students at SD Negeri 9 Mamboro.